Functional Training Handbook - Liebenson, Craig, ....- (Philadelphia : Wolters Kluwer, 2014)
Reach a whole new level of physical training with Functional Training Handbook, whose big-picture approach to movement fosters lifelong health, mobility, and athletic development. This practical guide delivers clear, how-to- information, an array of sport-specific guidelines, and key principles that will keep your clients at peak performance. Join the revolution to improve sports performance, treat injury, and re-train patterns with this comprehensive guide to the body and its movement. Features: Sport specific chapters include Baseball, Basketball, Cycling, Dance, Football, Golf, Hockey, Mixed Martial Arts, Olympic Weight Lifting, Skiing, Soccer, Swimming, Surfing, and Tennis. Emphasis on functional exercise explores the physics of weight-bearing and balance to reduce repetitive motion injuries Guides to injury prevention, safe workouts, re-injury avoidance, and practical strategies for active athletes Now with the print edition, enjoy the bundled interactive eBook edition, offering tablet, smartphone, or online access to: Complete content with enhanced navigation A powerful search that pulls results from content in the book, your notes, and even the web Cross-linked pages, references, and more for easy navigation Highlighting tool for easier reference of key content throughout the text Ability to take and share notes with friends and colleagues Quick reference tabbing to save your favorite content for future use
Keywords: Krachttraining